A snap of intimacy: Investigating photo sharing practices on Snapchat and Instagram - Larsen, Malene Charlotte; Kofoed, Jette (AoIR Selected Papers of Internet Research, 2016)
This paper investigates photo sharing practices on mobile social media platforms among Danish youth in three different age groups: Primary school students (aged 12-16), secondary school students (aged 16-19) and university students (aged 20-25). What kind of photos are exchanged in the different age groups on mobile photo sharing applications such as Snapchat and Instagram and what role do the photos play in processes of inclusion and exclusion? How are social relations maintained and altered in and by photo elicitation?Snapchat is a photo sharing app where the content self-destruct after a short while. Sometimes the content is screenshot by the viewer (and possibly shared again). Ephemeral social media such as Snapchat thus interrupts linear temporality and, we argue, plays with both temporality and intimacy. Instagram, on the contrary, can be described as a media where the content shared is persistent. I.e. the app allows the users to organize, use, document and remember in a persistent manner (Bayer et. al., 2015).In order to investigate photo sharing practices on Instagram and Snapchat we have employed an internet mediated mixed methods approach (Hesse-Biber & Griffin, 2013) combining both quantitative and qualitative data. Thus, the paper is based on group interviews and online fieldwork carried out since 2013 as well as data collected through an online survey in 2015 and 2016.